2006
DOI: 10.1002/bse.480
|View full text |Cite
|
Sign up to set email alerts
|

Do stakeholder groups influence environmental management system development in the Dutch agri‐food sector?

Abstract: This paper presents the results of a survey that included 492 companies in the Dutch agri-food sector with respect to the influence of stakeholder groups on the companies' level of environmental management system (EMS) implementation. It is concluded that primary stakeholders (government, clients) are more relevant for EMS development than secondary stakeholders (such as environmental organizations). The results suggest that small and medium-sized companies are able to accommodate to demands with respect to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 46 publications
(20 reference statements)
1
61
0
Order By: Relevance
“…Organizations, in turn, will have to publish their environmental policies in their mission, vision and values statements, as an essential means to inform the general public. In Holland, for example, Bremmers et al (2007) write that the government exerts pressure on all companies for the implementation of a system of environmental management in the entire supply chain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organizations, in turn, will have to publish their environmental policies in their mission, vision and values statements, as an essential means to inform the general public. In Holland, for example, Bremmers et al (2007) write that the government exerts pressure on all companies for the implementation of a system of environmental management in the entire supply chain.…”
Section: Discussionmentioning
confidence: 99%
“…T h e t h re e f u n d a m e n t a l t y p e s o f stakeholders that influence the adoption of CP in companies are: (i) government, through public policies (Ashford & Caldart, 2001;Bremmers, Omta, Kemp, & Haverkamp, 2007;Ciccozzi, Checkenya, & Rodriguez, 2003;Chiu, 2011;Geng, Xinbei, Qinghua, & Hengxin, 2010;Gravrilescu, 2004;Taylor, 2006;Zeng, Xu, Dong, & Tam, 2010); (ii) economic agents, comprised of company managers (Guerina, 2006;Hoff & Thiell, 2014), clients (Bremmers et al, 2007) and shareholders (Ciccozzi et al, 2003;O'Rourke, 2003;Zeng et al, 2010), and; (iii) society, concerned with the future of the environment (Guerina, 2006;Taylor, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma and Henriques (2005) identified the multiplicity of withholding influences (by regulators and environmental NGOs), usage influences (by customers) and employee influences (through involvement) were identified by managers. In addition to these influences, others were identified from internal, regulatory and supply-chain sources by Darnall et al (2009), whereas Bremmers et al (2007) found that primary stakeholders (such as the government and customers) are more relevant than secondary stakeholders such as environmental organisations. Delmas and Toffel (2004) identified customers, regulators, legislators, local communities and environmental activist organizations as influential stakeholders.…”
Section: Stakeholders' Environmental Demandsmentioning
confidence: 99%
“…Researchers have noticed variations of stakeholder influence on EMS development (Bremmers et al, 2007) and they have shown industry-based differences in managerial perceptions of corporate environmentalism. Accordingly, they have concluded that industries with high environmental impact have significantly greater levels of environmental orientation and strategy focus (Banerjee et al, 2003).…”
Section: Stakeholders' Environmental Demandsmentioning
confidence: 99%